Revoking documentary editors in the Algerian legislation: An analytical study - Assia, Hachemaoui (Journal of Economic, Administrative and Legal Sciences, 2021)
Documentary editors are extremely important in the comparative legal legislation , Being one of the basic proven guarantees of legal behavior and a proof to demonstrate the rights and obligations arising under the protection of the contractors , and it also has the authority to confront others , and given this importance , the legislator fortified it with a set of legal rules and regulations and whenever these conditions are met it gained an executive power and stability prevailed and whenever marred by a defect it lost its power and the rights of individuals and became vulnerable to nullification. Through this research, we will show cases of annulment of the documentary editors in the Algerian legislation and the legal implications of this. Both for the contracting parties or for the others who have acquired a right kind over the place of the contract that was decided to cancel it without prejudice to the rights of individuals legally protected.